Residents’ Support Intention through Event Attachment and Involvement in Urban Marathon Events - Risca Fitri Ayuni; Rila Anggraeni; M Abdi Dzil Ikhram W; Putu Adi Putra Arimbawa; Nadiyah Hirfiyana Rosita; Lintang Ayu Farah Atsila (SAFE-Network, 2026)
Urban marathon events are increasingly recognized as strategic tools for tourism promotion, city branding, and community engagement. Existing studies have predominantly focused on economic outcomes, with limited attention to how different levels of involvement perceive and respond to such events. This gap is important because residents’ support is critical to the long-term sustainability of recurring urban events, yet empirical evidence from the Indonesian context remains limited. This study aims to examine how multidimensional perceived benefits influence residents’ event attachment and support intention, while distinguishing between high- and low-involvement residents. This research employed a quantitative explanatory approach. The population consisted of residents living in marathon-hosting cities in Indonesia, and purposive sampling was used to select individuals aged 18 years and above who had knowledge of or exposure to the event. Data were collected from 320 residents across Jakarta, Bali, and Magelang and analyzed using Partial Least Squares Structural Equation Modeling and multi-group analysis in SmartPLS. The findings show that all perceived benefit dimensions significantly influence event attachment, with social and personal benefits emerging as the strongest predictors. Several key relationships were also found to be stronger among highly involved residents. These findings imply that marathon events should not only deliver visible benefits but also foster stronger emotional engagement and deeper resident involvement to build sustainable community support.